Strategy for Utilising Family Social Capital For Widows of Poso Conflict Victims 2008 - 2012 - Rosmawaty Rosmawaty; Hendra Hendra (HUMANISMA : Journal of Gender Studies, 2023)
This study aims to reveal the ways in which widows of conflict victims manage their assets and their abilities in an effort to survive and improve social welfare after the Poso conflict. Data were obtained from two sources: an analysis of literature during the Poso conflict and interviews with victims and their relatives. The results of the study show that widows in desperate situations save their lives from threats and riots by utilising social capital by relying on relatives with ownership. Assets and capabilities are linked by access and property ownership. This was built before the conflict occurred so as to strengthen the bonds of post-conflict social capital with kinship strength among the closest relatives, such as parents, siblings, and nephews or nieces, based on the same religion, for their survival.